Development of an Efficient Non‐Noble Metal Based Anode Electrocatalyst to Promote Methanol Oxidation Activity in DMFC. Issue 20 (27th May 2020) - Yaqoob, Lubna; Noor, Tayyaba; Iqbal, Naseem; Nasir, Habib; Zaman, Neelam; Rasheed, Lubna; Yousuf, Muhammad
Abstract: In this research, electrocatalytic activity of cobalt benzene tricarboxylic acid metal organic framework (Co BTC MOF) and its reduced graphene oxide based composites (rGO/Co BTC) were investigated in an alkaline media for the methanol oxidation reaction (MOR). Metal Organic frameworks (MOF) and their composites were solvothermally prepared and characterized via FTIR, EDX, SEM and XRD. Electrochemical studies were performed by cyclic voltammetry, electron impedance spectroscopy, chronoamperometry and cyclic stability. Among all the prepared composites, 1 wt % rGO/Co BTC MOF (1.07 mg cm −2 ) demonstrated a promising current density of 130 mA cm −2 at 1.59 V vs. RHE, a tafel slope of 83.6 mV dec −1 and resistance of 14.75 Ω in 1 M NaOH/ 2 M methanol solution showing much better performance than state‐of‐the‐art Pt based materials. Abstract : In this work electrocatalytic activity of Co BTC MOF and rGO based composites studied by cyclic voltammetry and electron impedance spectroscopy demonstrate a current density up to 130 mA cm −2 for 1 wt % rGO/Co BTC MOF at 1.59 V vs. RHE, and resistance of 14.75 Ω in 1 M NaOH/ 2 M methanol solution. Moreover, mass activity and tafel slope value for 1 wt % rGO composite was 17.19 and 83.6 mV dec −1 and stability was up to 17% as measured by chronoamperometry.